Strengthening Guatemala’s institutional response to climate-induced human mobility through capacity building and policy action - Pacillo, Grazia; Madurga Lopez, Ignacio (2025)
The Alliance of Bioversity and CIAT, through the CGIAR Research Initiative on Fragility, Conflict, and Migration (FCM), has strengthened Guatemala’s capacity to address climate-induced migration. By organizing national forums and training 54 civil servants, FCM improved inter-institutional coordination and stakeholders' understanding of climate, human mobility, and security. As a result, the Ministry of Environment (MARN) is co-developing a proposal with FCM to investigate drought‒migration linkages and identify integrated solutions to address the issue. The findings will inform policies to counter land degradation, enhance resilience, and improve food security and livelihoods, tackling key migration drivers.